(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Does the time of 21st century training necessitate exploration into emerging research pedagogies like design thinking for a better understanding of how design influences business and management? This review explains the changes in training perspectives within management settings using creative engagement methods like design thinking which call into question the future of dynamic business innovation. The paper undertakes a Systematic Literature Review of this nascent field, followed by a Bibliometric Analysis, Content Analysis to present a taxonomy of the field, and finally outlines interesting questions for future research to address.